Literary Heritage and European Identity - Hanenberg, Peter 1961- (2018)
Thomas Morus' Utopia, Luís de Camões' The Lusiads or Gotthold Ephraim Lessing's Nathan the Wise belong to the European canon - but are mostly read within their national linguistic contexts. It is necessary to recognize how much they have built a common European identity referring to concepts like critical thinking, the relation with extra-European cultures or tolerance. The module will suggest transnational readings of the literary heritage in its function as agent of promoting and translating European humanism.
Keywords: European Identity; imagined community; Literary heritage; Translation